Development of Systematic Land Use Planning Based on Seismic Microzonation: A Case Study on Miri district of Sarawak, Malaysia. - Najar, Imtiyaz Akbar (2020)
This study deals with the development of land-use planning based on seismic microzonation and it is a case study of Miri district of Sarawak, Malaysia. This study is timely for prevention of disaster, since Malaysia lies in the vicinity of regions (Sumatra, Indonesia, South Philippines and North Sulawesi) that have experienced strong earthquakes in the past. The main goal of this research is to develop the land-use planning map for future earthquakes to reduce the devastating effects of earthquake in the Miri district by utilizing the software geographical information system (ArcGIS). The highest peak ground acceleration of Sarawak is in Niah area of Miri district which is 0.15 g in terms of 10% probability of exceedance in 50 years corresponding to 2475 years return period. This research predominantly reports issues to provide the land-use planning of Miri district on the basis of seismic microzonation incorporated with site-specific ground response analysis and liquefaction susceptibility analysis. Seismic microzonation map was developed on the basis of seismic hazard assessment of Sarawak, geological and geotechnical aspects i.e. site response analysis and liquefaction susceptibility assessment by applying the analytical hierarchy process (AHP). 114 standard penetration test (SPT-N) boreholes were analysed across the Miri district. This study recognizes and inspects the factors in post-tremor land-use planning which can viably diminish the disastrous effects of earthquake in Miri district. Land-use is the main component to be utilized in this research. Processes and factors of land use administration planning is to clarify and analyze for the situation investigation of Miri district (Sarawak, Malaysia) to evaluate the applicability of land use management for earthquake calamity mitigation. From the results, it was found that the seismic hazard in the Miri district varies from low to high corresponding to 2475 years of return period with low to moderate as predominant over the Miri district. Only a few areas are under high hazard. Also, the land use planning map was compared with the current land use map acquired from satellite imagery and it was found that all built up is in the low hazard area. The “land-use planning” can be introduced in the Malaysian National Annex to Eurocode 8 (MNA-EC8) for the better planning of design of structures and the resistance of earthquakes.